2003
DOI: 10.1152/ajplung.00316.2002
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization ofPseudomonaspyocyanin cytotoxicity in human lung epithelial cells

Abstract: The Pseudomonas aeruginosa secretory product pyocyanin damages lung epithelium, likely due to redox cycling of pyocyanin and resultant superoxide and H2O2 generation. Subcellular site(s) of pyocyanin redox cycling and toxicity have not been well studied. Therefore, pyocyanin's effects on subcellular parameters in the A549 human type II alveolar epithelial cell line were examined. Confocal and electron microscopy studies suggested mitochondrial redox cycling of pyocyanin and extracellular H2O2 release, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 52 publications
8
64
1
Order By: Relevance
“…As determined from measurements of ⌿ cyto , [PYO] as low as 1 M caused small oxidation of ⌿ cyto , and 10 and 100 M PYO caused large and sustained oxidation of ⌿ cyto by 20 and 40 mV. These quantitative measurements of PYO-induced oxidation of the cytosol therefore confirm previous qualitative measurements based on the use of oxidation-dependent fluorescein derivatives (21,22) or electron spin resonance (16) . at concentrations that oxidized the cytosol similar to that exhibited by 100 M PYO (i.e.…”
Section: Pyo Triggers Production Of Cellular H 2 O 2 Thatsupporting
confidence: 84%
See 2 more Smart Citations
“…As determined from measurements of ⌿ cyto , [PYO] as low as 1 M caused small oxidation of ⌿ cyto , and 10 and 100 M PYO caused large and sustained oxidation of ⌿ cyto by 20 and 40 mV. These quantitative measurements of PYO-induced oxidation of the cytosol therefore confirm previous qualitative measurements based on the use of oxidation-dependent fluorescein derivatives (21,22) or electron spin resonance (16) . at concentrations that oxidized the cytosol similar to that exhibited by 100 M PYO (i.e.…”
Section: Pyo Triggers Production Of Cellular H 2 O 2 Thatsupporting
confidence: 84%
“…Altering the redox properties of the endoplasmic reticulum could trigger an unfolded protein response that leads to activation of NF-B (37), but PYO did not activate the unfolded protein response (analyzed by IRE1␣-dependent splicing of XBP-1), 3 indicating that this was an unlikely explanation for the mechanism by which PYO synergizes with NF-B-activating agonists in stimulating NF-B. Previous work has indicated that PYO may oxidize mitochondria selectively (22), and such oxidation could couple to cytosolic signaling (38) to activate NF-B. By using mitochondria-targeted roGFP, we found that PYO oxidized mitochondrial redox potential (⌿ mito ), although about 20% less than ⌿ cyto , 3 indicating that PYOinduced oxidation of ⌿ mito could contribute to activation of NF-B.…”
Section: Pyo Triggers Production Of Cellular H 2 O 2 Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is essential in the mitochondrial respiratory chain and is repressed under iron-deficient conditions and when there is a lack of heme groups (Dorsman and Grivell, 1990). In addition to the repression of these enzymes, it is possible that the Krebs cycles of C. albicans in mixed biofilms is affected by pyocyanin (Figure 8), which has been demonstrated to block respiration by inhibiting the activity of aconitase and affect the membrane potential of mitochondria from human cells (O'Malley et al, 2003).…”
Section: Albicans Respiration Proteins Are Downregulated In Mixed mentioning
confidence: 99%
“…Because PCA is structurally similar to pyocyanin, we initially hypothesized that PCA may exert prooxidant effects in mammalian cells. Thus it was of interest to determine whether PCA, like pyocyanin (9,11,28), stimulates intracellular oxidant formation in human airway epithelial cells.…”
Section: L586mentioning
confidence: 99%